2010
DOI: 10.3171/2009.11.spine09264
|View full text |Cite
|
Sign up to set email alerts
|

Anterior bone cement augmentation in anterior lumbar interbody fusion and percutaneous pedicle screw fixation in patients with osteoporosis

Abstract: Anterior PMMA augmentation during instrumented ALIF in patients with osteoporosis was useful to prevent cage subsidence and vertebral body collapse. In addition, PMMA augmentation did not increase the nonunion rate and incidence of ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…Indeed, such efforts have boosted fusion rates. 2,13,14,16,32 Stand-alone cages with intrinsic plates and screws have also been developed to address needed restoration of the anterior tension band. 15 Cage stability in flexion, extension, and lateral bending now compares favorably with pedicle screw fixation and is superior with respect to rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such efforts have boosted fusion rates. 2,13,14,16,32 Stand-alone cages with intrinsic plates and screws have also been developed to address needed restoration of the anterior tension band. 15 Cage stability in flexion, extension, and lateral bending now compares favorably with pedicle screw fixation and is superior with respect to rotation.…”
Section: Discussionmentioning
confidence: 99%
“…20,25,33 Furthermore, the use of prophylactic anterior cement augmentation has been shown to decrease cage subsidence following ALIF and PSF in osteoporotic patients. 8 Cement augmentation does have associated risks that are particularly prone to occur in osteoporotic patients. Reports of failed cement-augmented instrumentation exist, and potential consequences can be more drastic than nonaugmented screws, as the intact cement-screw complex can be displaced through compromised bone.…”
Section: 18mentioning
confidence: 99%
“…6 Prior studies have described ALIF with cement augmentation and supplemental posterior fixation for these osteoporotic patients, but the two-site approach when using traditional techniques to place posterior instrumentation has been associated with longer operative time, increased blood loss, and increased complication rates. [7][8][9] Specifically with percutaneous pedicle screw placement, there is greater radiation exposure and violation of cranial facet joints, which can lead to altered biomechanics at the adjacent level. 10 Other studies have shown pseudoarthrosis rates from 0% to 49% in ALIFs without supplemental posterior fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsidence of a stiff anterior spinal implant into the weaker vertebral body is often observed in clinical practice [1][2][3][4][5][6]. This alteration may occur shortly after surgery or can develop typically within approximately one year [4].…”
Section: Introductionmentioning
confidence: 99%
“…A single or a small number of high spinal loads that cause stress that exceeds the strength of the bone are most likely the reason for early subsidence, whereas long-term subsidence is caused by repeated loads that cause stresses that are below the ultimate static bone strength. Osteoporotic vertebral bodies are more vulnerable to implant subsidence than are normal ones owing to the reduced bone strength [3,6]. The amount of subsidence may vary widely.…”
Section: Introductionmentioning
confidence: 99%